Transformation rules in Boolean algebra

In summary: P, I have edited it. We conclude that [P/\-Q] is equivalent to P because we have assumed P, and as P-->P, then we can say that P is equivalent to [P/\-Q].
  • #1
Raghav Gupta
1,011
76
I know De-Morgan's law that $$ -(p∧q) = -p∨-q $$
Also $$ -(p∨q) = -p∧-q $$
But for material implication and bi conditional operations there are also some transformation.
What is the law or proof for it? Like
$$ p⇒q = -p∨q $$
$$ p ↔q = (p∧q) ∨ (-p∧-q) $$
There may be other properties also that I don't know.
How one can derive or say that?

SideNote: Why PF don't have a negation ( tilda symbol) ?
 
Physics news on Phys.org
  • #2
Raghav Gupta said:
I know De-Morgan's law that $$ -(p∧q) = -p∨-q $$
Also $$ -(p∨q) = -p∧-q $$
But for material implication and bi conditional operations there are also some transformation.
What is the law or proof for it? Like
$$ p⇒q = -p∨q $$
$$ p ↔q = (p∧q) ∨ (-p∧-q) $$
There may be other properties also that I don't know.
How one can derive or say that?

SideNote: Why PF don't have a negation ( tilda symbol) ?

This should strictly be logical equivalence and not equality.
You can show $$ p⇒q = -p∨q $$ , e.g., with truth tables, showing that the two associated tables are identical, or by using a derivation, assuming $$ p⇒q $$ and deriving $$-p∨q $$ from it. Example: rewrite$$ -p ∨ q = -(p ∧-q)$$ , and assume p , then assume $$ (p ∧-q)$$, and arrive at a contradiction . From previous, p follows, then q follows and then you conclude$$ q ∧-q $$ , a contradiction, from which $$ -(p ∧-q) $$ follows.
 
Last edited:
  • #3
WWGD said:
assuming $$ p⇒q $$ and deriving $$-p∨q $$ from it. Example: rewrite$$ -p ∨ q = -(p ∧-q)$$ , and assume p , then assume (within the assumption of p)$$ (p ∧-q)$$ . From p, q follows and then you conclude$$ q ∧-q $$ , a contradiction, from which $$ -(p ∧-q) $$ follows.
rewrite$$ -p ∨ q = -(p ∧-q)$$
That you have written by De-Morgan's Law. Then I am not able to understand afterwards.
 
  • #4
I just rewrote. Please point out the steps you don't understand. I want to show A->B, and I do that by trying to show A-> -B, i.e., I assume A, and I assume it implies -B, and arriving at a contradiction from this last. Here B is (p∧-q) and A is $$ p⇒q $$ . It is a proof by contradiction.
 
Last edited:
  • #5
I am not understanding that,
If A is $$ p ⇒q $$ and B is $$ p ∧-q $$ then how A implying -B is a contradiction?
 
  • #6
If you assume A ->B and you arrive at a contradiction, then you can conclude A--> -B. In our case, if you assume (P-->Q)-> -[ P/\-Q] and you derive a contradiction from that, then, by contradiction, you conclude (P-->Q)->[P/\-Q].

So what we do is: we assume that (P-->Q) implies the negation of what we want to prove, i.e., we assume that (P-->Q) -->-[P/\-Q] and from this we arrive at a contradiction, then we conclude (P-->Q)-->-(-[P/\-Q])==[P/\-Q].
 
Last edited:
  • #7
More Formally/ in more detail:

We assume P-->Q and we assume -[-P \/ Q]=[P/\-Q] , i.e., we assume (P-->Q)-->[P/\-Q] , and from this we arrive at a contradiction, from which we conclude

(P-->Q)-->[P/\-Q] ==[-P\/Q]:

Assume
(P-->Q)--> [P/\-Q] , and assume (P-->Q)
i) Then we conclude [P/\-Q] == P
ii) From [P/\-Q] ,we conclude P
iii) From [P/\-Q] , we conclude- Q
iv) From ii and the premise, we conclude Q
v)From iv) and iii) , we conclude Q/\-Q , a contradiction
vi)By contradiction, we conclude -[P/\-Q]
___________________________________ We discharge our assumption, to get:

(P-->Q) --> -[[P/\-Q]]==-P \/ Q

Which is what we wanted to show.
 
  • #8
I think it is better to go by truth table.
I am able to show they are both equivalent by truth table. I am not able to understand these statements much.
Why we are in the first place going for a proof by contradiction?
WWGD said:
Assume
(P-->Q)--> [P/\-Q] , and assume (P-->Q)
i) Then we conclude [P/\-Q] == P
ii) From [P/\-Q] ,we conclude P
iii) From [P/\-Q] , we conclude- Q
iv) From ii and the premise, we conclude Q
v)From iv) and iii) , we conclude Q/\-Q , a contradiction
vi)By contradiction, we conclude -[P/\-Q]
___________________________________ We discharge our assumption, to get:

(P-->Q) --> -[[P/\-Q]]==-P \/ Q

Which is what we wanted to show.
I am not understanding the first point that how we are concluding [PΛ-Q]== P ?
 
  • #9
My mistake, should be just [P/\-Q]
 

1. What are the basic transformation rules in Boolean algebra?

The basic transformation rules in Boolean algebra include the commutative, associative, and distributive laws. These rules allow for rearranging and simplifying logical expressions without changing their truth value.

2. How do the commutative and associative laws work in Boolean algebra?

The commutative law states that the order of operands in a logical expression does not affect its truth value. This means that the order of operations can be changed without changing the result. The associative law states that the grouping of operands in a logical expression does not affect its truth value. This means that parentheses can be moved without changing the result.

3. What is the distributive law in Boolean algebra?

The distributive law states that an expression can be distributed over a logical operator. For example, A AND (B OR C) is equivalent to (A AND B) OR (A AND C). This rule is useful for simplifying complex expressions and can be extended to multiple operators.

4. How do transformation rules help simplify logical expressions?

Transformation rules in Boolean algebra allow for the manipulation and rearrangement of logical expressions without changing their truth value. By applying these rules, complex expressions can be simplified and made easier to understand and evaluate.

5. Are there any other important transformation rules in Boolean algebra?

Yes, there are other important transformation rules in Boolean algebra such as De Morgan's laws, which state that the negation of a logical expression is equivalent to the opposite operator being applied to each individual term. Additionally, the identity and complement laws are also essential in simplifying logical expressions.

Similar threads

  • Set Theory, Logic, Probability, Statistics
Replies
6
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
3K
  • Linear and Abstract Algebra
Replies
1
Views
827
  • Set Theory, Logic, Probability, Statistics
Replies
4
Views
2K
  • General Math
Replies
2
Views
1K
  • Set Theory, Logic, Probability, Statistics
2
Replies
40
Views
6K
  • Quantum Interpretations and Foundations
2
Replies
47
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
2
Views
8K
  • Precalculus Mathematics Homework Help
Replies
4
Views
748
Back
Top